2015
DOI: 10.1002/chem.201503074
|View full text |Cite
|
Sign up to set email alerts
|

Coating Platinum Nanoparticles with Methyl Radicals: Effects on Properties and Catalytic Implications

Abstract: It was recently reported that the reaction of methyl radicals with Pt(0) nanoparticles (NPs), prepared by the reduction of Pt(SO4)2 with NaBH4, is fast and yields as the major product stable (Pt(0)-NPs)-(CH3)n and as side products, in low yields, C2H6, C2H4, and some oligomers. We decided to study the effect of this coating on the properties of the Pt(0)-NPs. The results show that the coating can cover up to 75% of the surface Pt(0) atoms. The rate constant of the reaction, k((.)CH3+Pt(0)-NPs), decreases with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…The pH values of these suspensions were 8.9 ± 0.3 and 6.9 ± 0.3 for the Pd 0 ‐NPs and the Au 0 ‐NPs, respectively. Their final particle concentrations, calculated from these measurements, in a procedure identical to that described previously, were 1.25 × 10 –7 m for the Pd 0 ‐NPs and 1.73 × 10 –7 m for the Au 0 ‐NPs , …”
Section: Methodsmentioning
confidence: 99%
“…The pH values of these suspensions were 8.9 ± 0.3 and 6.9 ± 0.3 for the Pd 0 ‐NPs and the Au 0 ‐NPs, respectively. Their final particle concentrations, calculated from these measurements, in a procedure identical to that described previously, were 1.25 × 10 –7 m for the Pd 0 ‐NPs and 1.73 × 10 –7 m for the Au 0 ‐NPs , …”
Section: Methodsmentioning
confidence: 99%
“…[15,16] Methyl radicals are proposed to be the surface reaction intermediates in the partial oxidation of methane to methanol and formaldehyde. [17] Recently, [18,19] it was shown that platinum nanoparticles (Pt 0 -NPs) suspended in aqueous solutions react with methyl radicals differently than with other noblemetal NPs such as gold and silver, [20,21] and the major reaction with Pt 0 -NPs is [Eq. (1)]:…”
mentioning
confidence: 99%
“…Thes urface layer of methyl groups can be released as methane through reaction of (Pt 0 -NPs)-(CH 3 ) n with H 2 . [19] Among the various chemical properties of Pt and Pd nanostructures, their interaction with Hi se specially important, because Pd is regarded as am aterial for hydrogen storage [22] and because Pt and Pd NPs are widely used to catalyzer eactions involving elementary steps of hydrogenationand dehydrogenation. [23,24] Hydrogen adsorption on Pt 0 is known to occur at different sites [25][26][27] on the surface of the bulk metal and Pt 0 -NPs to be in equilibrium in water with H 3 O + , [28] to cause changes in the surface structures, [29,30] andt oa ffect the catalytic properties of the platinum catalysts [31] and the electrocatalysts.…”
mentioning
confidence: 99%
See 2 more Smart Citations